The Interplay Between Non-Esterified Fatty Acids and Bovine Peroxisome Proliferator-Activated Receptors: Results of an In Vivo-In Vitro Hybrid Approach. (29th May 2020) - Busato, Sebastiano; Bionaz, Massimo
Abstract: Objectives: Metabolic stressors and energy deficiency related to parturition induce lipolysis in dairy cows with a subsequent increase in circulating non-esterified fatty acids (NEFA ). We hypothesized that circulating NEFA directly activate the Peroxisome Proliferator-Activated Receptors (PPAR ), a transcription factor with known nutrigenomics response to fatty acids, in a dose-dependent manner. Methods: Whole-blood samples were collected from five cows at different times between −40 and +10 days relative to parturition to isolate serum. NEFA were extracted from said samples through solid-phase extraction. A bioluminescent reported, bound to a PPAR response element, was used to assess PPAR activation in response to the treatments. To estimate individual PPAR isotype activation, PPAR isotype-specific antagonists were used, along with the treatments. Results: Isolated NEFA activate PPAR linearly up to 400 μM, with a decrease in their effect when albumin is introduced. A hybrid approach, treating cells with bovine serum from different stages of parturition, revealed that much of the PPAR activation can be explained by the amount of NEFA in the serum, and that its activation follows a quadratic tendency (calculated maximum activation at 1.47 mM NEFA of 4.8-fold vs. DMEM control, R 2  = 0.91). Further analysis of the effect of serum NEFA on PPAR revealed that they mostly activate PPARδ and PPARγ, but not PPARα. However, addition of palmitic acid to the media activate PPARδ and PPARα, but not PPARγ, and only when circulating NEFA are low (0.16 mM, prepartum), while additional palmitate did not increase PPAR activation in serum with high NEFA (0.71 mM, postpartum). Finally, the addition of lipoprotein lipase to the serum, in order to mimic release of NEFA from VLDL, increased PPAR activation, recapitulating the role of dietary lipids in the regulation of PPAR. Conclusions: Taken together, our results support the activation of PPAR by NEFA, helping to explain prior observations on PPAR activation in peripartum cows. Additionally, we outlined the role of dietary fatty acids in activating PPAR and their interaction with serum NEFA. Our results aid in setting the foundation for nutrigenomics approaches in ruminant nutrition. Funding Sources: This study was funded by the Oregon Beef Council.